1998
DOI: 10.1093/intqhc/10.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Elderly patients with heart failure: a study of satisfaction with care and quality of life

Abstract: This finding has supported our hypothesis that a higher level of quality of life would be related to fewer readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 5 publications
3
12
0
1
Order By: Relevance
“…The prevalence of HF rises from 2% to 3% at age 65 to more than 80% in persons over 80 years of age (537), and HF is the most common reason for hospitalization in elderly patients (538)(539)(540)(541). The high prevalence of HF in the elderly may be associated with age-related changes in ventricular function (particularly diastolic function) and to the cumulative effects of hypertension and other chronic risk factors (542)(543)(544)(545)(546).…”
Section: Elderly Patientsmentioning
confidence: 99%
“…The prevalence of HF rises from 2% to 3% at age 65 to more than 80% in persons over 80 years of age (537), and HF is the most common reason for hospitalization in elderly patients (538)(539)(540)(541). The high prevalence of HF in the elderly may be associated with age-related changes in ventricular function (particularly diastolic function) and to the cumulative effects of hypertension and other chronic risk factors (542)(543)(544)(545)(546).…”
Section: Elderly Patientsmentioning
confidence: 99%
“…In our study, there was significant association between age and satisfaction with current services (p=0.012) but no significant association with state of health. In a study conducted by Candlish et al (1998), elderly patients were the most likely to be satisfied compared with younger patients. 24 In fact, regarding association between age and patient satisfaction, a review by Dayasiri and Lekamgein (2010), which focused on patient satisfaction in Asian hospitals, showed that only few studies reported an effect of age on the satisfaction while the majority of studies reported no association.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Candlish et al (1998), elderly patients were the most likely to be satisfied compared with younger patients. 24 In fact, regarding association between age and patient satisfaction, a review by Dayasiri and Lekamgein (2010), which focused on patient satisfaction in Asian hospitals, showed that only few studies reported an effect of age on the satisfaction while the majority of studies reported no association. 25 Regarding state of health, Bleich et al (2009) also reported in their study that patients with bad or moderate health were the least satisfied with the services compared with those who had a good state of health.…”
Section: Discussionmentioning
confidence: 99%
“…Despite conflicting evidence of the value of readmission as a quality metric, there are substantial data indicating patients report improved quality of life when they are not readmitted. In a study of CHF patients, those readmitted reported significantly lower quality of life at 12 mo versus nonreadmitted counterparts [43]. Fazio et al [44] reviewed their ileoanal pouch data from 1984e2008 and determined patients admitted within 30 d of surgery had significantly lower Cleveland Global Quality of Life scores.…”
Section: Discussionmentioning
confidence: 99%